Counter-narratives of achievement at South Africa’s first apartheid-era black medical school, 1950s to the early 1990s (Historia, 2021)
EnglishThis article examines the construction and dissemination of two particular achievement narratives – one focused on high academic standards, the other on a Black Consciousness-inspired “Black pride” – that were produced by academic staff and students at the University of Natal’s Medical School, South Africa’s first apartheid-era black medical school in the highly racialised context of the 1950s to early 1990s. While quite different in terms of their producers and periods of origin, the article argues that both these narratives developed with a similar purpose: as counter-narratives, which intended to critique or challenge the pervasive and disparaging apartheid-era discourse that portrayed black South Africans as inferior. Indeed, both these narratives sought, in their own respective ways, to enable those producing them to reframe the dominant apartheid discourse, to offer alternatives, including more positive views about black South Africans, and to take an oppositional stance. Yet, while both developed as counter-narratives, they did so with different emphases and stances taken to challenge apartheid, highlighting the complexity of these narratives. In addition, this article examines how both these narratives could sometimes, in particular historical moments, overlap in time and even amalgamate, leading to the construction of hybridised narratives.    AfrikaansIn hierdie artikel word die konstruksie en verspreiding van twee besondere prestasienarratiewe bestudeer – een gerig op hoë akademiese standaarde, die ander op ’n Black Consciousness-geïnspireerde “Black pride” (Swart hoogmoed”) – wat vervaardig is deur akademiesepersoneel en studente aan die Universiteit van Natal se Mediese Skool, Suid-Afrika se eerste swart mediese skool in die apartheids tydperk in die hoogs rassise konteks van die 1950s tot vroeë 1990s. Alhoewel dit heel anders is met betrekking tot hul produsente en oorsprongstydperke, voer hierdie artikel aan dat albei hierdie vertellings met ’n soortgelyke doel ontwikkel het: as teen verhale, wat bedoel was om die deurdringende en neerhalende diskoers van die apartheid tydperk wat swart Suid-Afrikaners uitbeeld, te kritiseer of uit te daag as minderwaardig. Inderdaad, albei hierdie vertellings het op hulle eie maniere probeer om diegene wat hulle produseer in staat stel om die dominante apartheids diskoers te herformuleer, alternatiewe aan te bied, meer positiewe sienings oor swart Suid-Afrikaners te vorm en ’n opposise-standpunt in te neem. Alhoewel albei as teenverhale ontwikkel het, het hulle dit gedoen met verskillende beklemtonings en standpunte om apartheid uit te daag wat die kompleksiteit van hierdie vertellings beklemtoon. Daarbenewens word in hierdie artikel gekyk hoe albei hierdie vertellings, soms in die besonder historiese momente in tyd, kan oorvleuel en selfs kan saamsmelt, wat kan lei tot die konstruksie van hibridiese vertellings.
Keywords: Counter-narratives; medical education; University of Natal Medical School; apartheid; South African Students’ Organisation (SASO); Black Consciousness; Teen narratiewe; mediese opleiding; Universiteit van Natal Mediese Skool